Estudio sobre la percepción de la publicidad en televisión de la Empresa de Telefonía Celular Alegro PCS en el cantón Santo Domingo Primer Trimestre Año 2010 - Muñoz Cruz, Gustavo Wilfrido (2011)
An announcement transmitted by television can, at sight of many, to be innocent; nevertheless, it brings with itself a series of elements that cause in the viewer diverse conduct factors, between which, it’s perception that includes the form in which people catch the advertising messages. In this thesis, it will be able to appraise a study on the form in which a commercial one is perceived and understood by the consumer to whom they motivate to the acquisition either of a service, goods or a product. I invite you to this little trough perception of publicity and the behavior of consumers before it.